Change Management On The Implementation Of Artificial Intelligence (Ai) In Sharia Entrepreneurs In The Industrial Era 4.0 - Adelika, Adelika (Jurnal Fokus Manajemen, 2024)
In the 4.0 era, there has been a striking digitalisation revolution. Machines have been replaced by artificial intelligence (AI). In the past, humans did the thinking, but now robots also have the ability to think, and this will become more common in the future. Industrial Revolution 4.0 differs from previous revolutions in that it involves advances in artificial intelligence (AI), robotics, Internet of Things (IoT), 3D printing, genetic engineering, quantum computing and other technologies. Artificial intelligence is a technology created to mimic human intelligence, with a focus on developing the ability of machines to think and work like humans. Examples of artificial intelligence are speech recognition, problem solving, learning, and planning. However, the use of artificial intelligence (AI) also has a negative impact, namely the reduction of jobs affecting human resources. The question that arises is whether artificial intelligence can adapt the Sharia concept that has long been applied in Indonesia?